WOMEN RIGHTS IN THE CURRENT DAYS OF THE REPUBLIC OF UZBEKISTAN AND THEIR PROSPERITY - A. N. Gulyamova (Western European Studies, 2025)
Women's rights are an integral part of human rights, and their equal participation in social, economic, and political life is a fundamental characteristic of any democratic society. In Uzbekistan, the protection and development of women's rights is a priority in state policy. In Uzbekistan, women's rights and their role in society are one of the priorities of state policy. The country pays great attention to protecting the rights and interests of women, increasing their socio-political and economic activity.
Keywords: Uzbekistan; political; protecting